The effect of cooperative Jahn–Teller interactions on C60− anions - Moujaes, Elie A.; Dunn, Janette L. (IOP Publishing, 2010)
Singly charged buckminsterfullerene anions, C60−, are subject to a strong intramolecular T [circle times] h Jahn–Teller (JT) effect. When such ions interact with other C60− ions in a solid through a cooperative JT effect, they will be subject to an additional interaction. There are a number of different mechanisms that can cause this interaction. However, in the molecular field approximation, all can be modelled phenomenologically in terms of a symmetry-lowering interaction written in terms of a linear combination of electronic operators for the h modes involved in the intramolecular JT effect. We will consider the combined effect of this distortion and the intramolecular JT effect. We will analyse the lowest adiabatic potential energy surface, and calculate the energies of the resultant vibronic states. The results are shown to have a complicated dependence on the particular combination of h modes chosen, and the energies of the resultant vibronic states cannot easily be deduced from the form of the potential alone.